2018
DOI: 10.20471/acc.2018.57.03.21
|View full text |Cite
|
Sign up to set email alerts
|

Primary Epithelioid Hemangioendothelioma in the Cerebellum: Case Report with Reference to Drastic Change in the WHO Classification

Abstract: SUMMARY – Epithelioid hemangioendothelioma is a rare vascular brain tumor. It develops from endothelial cells, usually in the liver, lung, bone and soft tissue. Primary localization of this tumor in the intracranial space is very uncommon; only 47 cases have been described in the literature. This tumor was initially classified as grade I (benign) in the World Health Organization ( WHO) 2007 classification. In 2016, this tumor was re-classified as grade III (malignant). Herein, the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…[96] A review of the literature revealed 61 cases of primary intracranial EHE [Table 2]. [2,3,6,7,9,10,16,18,23,26,27,29,30,33,35,38,40,43,45,47,53,54,57,59,[62][63][64][65][66][67][68][70][71][72][73]76,79,[82][83][84][85][86]89,92,94,95,98,99,101,104,105] ere is a wide age range (31 weeks gestation-74 years ...…”
Section: Discussionmentioning
confidence: 99%
“…[96] A review of the literature revealed 61 cases of primary intracranial EHE [Table 2]. [2,3,6,7,9,10,16,18,23,26,27,29,30,33,35,38,40,43,45,47,53,54,57,59,[62][63][64][65][66][67][68][70][71][72][73]76,79,[82][83][84][85][86]89,92,94,95,98,99,101,104,105] ere is a wide age range (31 weeks gestation-74 years ...…”
Section: Discussionmentioning
confidence: 99%
“…Epithelioid haemangioendothelioma was initially believed to be an aggressive form of bronchoalveolar cell carcinoma invading adjacent blood vessels and small airways, hence the name intravascular bronchioloalveolar tumour (9,10). However, the development of pathology proved that EHE could occur anywhere in the body, such as the liver, lungs, skin, bone, spleen, pleura, lymph nodes, thyroid, parotid gland, and cerebellum (11)(12)(13). In the 2020 WHO classification of sarcomas, EHE is distinguished from other vascular tumours and defined as an independent disease (5).…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative misdiagnosis of EHE is usually due to its low incidence, lack of specific oncological markers, and unclear pathogenesis (1,13). However, the improvement of medical imaging equipment and diagnostic technology has made it possible for medical imaging, including CT, MRI, and F-FDG-PET to show certain pathological characteristics of EHE (1,(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelioid hemangioendothelioma (EHE) is a rare vascular tumor, accounting for less than 1% of all vascular tumors. 1 , 2) EHE is most often found in the lung, liver, and bones, and is rarely located in the skull base, dura, or brain parenchyma. 1 , 2) To date, no previous reports have described EHE of the spinal cord, although there was a report of EHE of the filum terminale.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2) EHE is most often found in the lung, liver, and bones, and is rarely located in the skull base, dura, or brain parenchyma. 1 , 2) To date, no previous reports have described EHE of the spinal cord, although there was a report of EHE of the filum terminale. 3) The authors here report the first case of EHE of the thoracic spinal cord.…”
Section: Introductionmentioning
confidence: 99%